An observational study of bail decision-making - Allan, Alfred (Psychiatry, psychology and law, 2005)
Pre-trial detention of defendants has important legal, human rights and practical implications for defendants, their families, and society and therefore the area justifies research scrutiny. However, there is a dearth of empirical studies of bail decision-making and most of them have been retrospective studies. Prior studies have nevertheless identified a number of purported shortcomings in bail legislation and decision-making. The rarely used observational methodology employed in this study provided data that are not normally available from official records. The first appearances of 648 defendants were observed in the lower courts in metropolitan Perth (Western Australia) to identify factors that play a significant role in bail decision-making and to collect baseline data for a longitudinal study. Legal factors made a significant contribution to the bail decision, while extra-legal factors did not